Axillary versus innominate artery cannulation for antegrade cerebral perfusion in aortic surgery: design of the Aortic Surgery Cerebral Protection Evaluation (ACE) CardioLink-3 randomised trial. Issue 6 (10th June 2017) - Garg, Vinay; Peterson, Mark D; Chu, Michael WA; Ouzounian, Maral; MacArthur, Roderick GG; Bozinovski, John; El-Hamamsy, Ismail; Victor Chu, F; Garg, Ankit; Hall, Judith; Thorpe, Kevin E; Dhingra, Natasha; et al.
Abstract : Introduction: Neurological injury remains the major cause of morbidity and mortality following open aortic arch repair. Systemic hypothermia along with antegrade cerebral perfusion (ACP) is the accepted cerebral protection approach, with axillary artery cannulation being the most common technique used to establish ACP. More recently, innominate artery cannulation has been shown to be a safe and efficacious method for establishing ACP. Inasmuch as there is a lack of high-quality data comparing axillary and innominate artery ACP, we have designed a randomised, multi-centre clinical trial to compare both cerebral perfusion strategies with regards to brain morphological injury using diffusion-weighted MRI (DW-MRI). Methods and analysis: 110 patients undergoing elective aortic surgery with repair of the proximal arch requiring an open distal anastamosis will be randomised to either the innominate artery or the axillary artery cannulation strategy for establishing unilateral ACP during systemic circulatory arrest with moderate levels of hypothermia. The primary safety endpoint of this trial is the proportion of patients with new radiologically significant ischaemic lesions found on postoperative DW-MRI compared with preoperative DW-MRI. The primary efficacy endpoint of this trial is the difference in total operative time between the innominate artery and the axillary artery cannulation group. Ethics and dissemination: The study protocol and consent forms have been approved by the participating local research ethics boards. Publication of the study results is anticipated in 2018 or 2019. If this study shows that the innominate artery cannulation technique is non-inferior to the axillary artery cannulation technique with regards to brain morphological injury, it will establish the innominate artery cannulation technique as a safe and potentially more efficient method of antegrade cerebral perfusion in aortic surgery. Trial registration number: NCT02554032.